1998
DOI: 10.1006/viro.1998.9360
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Transport of Intact Poliovirus Through the Axon via the Fast Transport System

Abstract: Intramuscularly inoculated poliovirus is thought to spread to the central nervous system through neural pathways in humans, monkeys, and the transgenic (Tg) mice carrying the human poliovirus receptor (PVR) gene. To gain insight into molecular mechanisms for the retrograde axonal transport of poliovirus, resulting in the expression of neurovirulence, a poliovirus-sensitive ICR-PVRTg21 mouse line (Tg21) was used as an animal model for poliomyelitis. We detected poliovirus antigens in axons of the sciatic nerve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 24 publications
8
93
1
2
Order By: Relevance
“…Previous studies have shown that neurotropic viruses can initiate infection in the periphery and can move through peripheral neurons to reach the central nervous system (Card et al, 1991;Ohka et al, 1998;Samuel et al, 2007;Tyler et al, 1986). Therefore, we hypothesized that mice with neurotropic disease may have higher viral titres in peripheral neurons and brain.…”
Section: Yfv-17d Titres In Ifnar "/" Micementioning
confidence: 91%
“…Previous studies have shown that neurotropic viruses can initiate infection in the periphery and can move through peripheral neurons to reach the central nervous system (Card et al, 1991;Ohka et al, 1998;Samuel et al, 2007;Tyler et al, 1986). Therefore, we hypothesized that mice with neurotropic disease may have higher viral titres in peripheral neurons and brain.…”
Section: Yfv-17d Titres In Ifnar "/" Micementioning
confidence: 91%
“…PV is transported retrogradely by the fast axonal transport system, and PV antigen is detected inside axons (35). However, it is still unclear whether PV is enclosed in vesicles during its transport, although vesicles are known to be conveyed by the fast axonal transport system (6).…”
Section: Pv Endocytosis At Neuromuscular Junctions Of the Tg Mousementioning
confidence: 99%
“…In that study, it was demonstrated that circulating PV after intravenous inoculation appears to cross the blood-brain barrier at a high rate, and the neural dissemination pathway from the skeletal muscle is not the primary dissemination route of the circulating virus to the central nervous system. Along with this pathway of dissemination, a neural pathway has been reported in humans (32), monkeys (20), and PV-sensitive transgenic (Tg) mice carrying the human PV receptor (hPVR/ CD155) gene (35,36), and it appears to be important in causing provocation poliomyelitis (14). Using the Tg mouse line, we demonstrate that PV inoculated into the calf is incorporated into the sciatic nerve and retrogradely transported through the axons as intact virion particles, that one of the fast retrograde axonal transport systems is involved in viral dissemination, and that the pathogenesis of PV infection via the neural pathway is inhibited by the anti-hPVR monoclonal antibody (MAb) p286, which is able to block the infection (35).…”
mentioning
confidence: 99%
“…inoculation (24,25) or through viremia concomitant with skeletal muscle injury (16) is a known factor facilitating PV CNS invasion. Retrograde axonal transport of virus mediated by peripheral entry at the neuromuscular junction (NMJ) is suspected to account for this effect (16), because paralysis typically originates in the injected limb (the ''localization'' phenomenon; ref.…”
Section: Cns Invasion Via Retrograde Axonal Transportmentioning
confidence: 99%